2020
DOI: 10.1101/2020.10.28.20220657
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High performance of a novel antigen detection test on nasopharyngeal specimens for SARS-CoV-2 infection diagnosis: a prospective study

Abstract: Introduction The SARS-CoV-2 pandemic has become a major public health issue worldwide. Developing and evaluating rapid and easy-to-perform diagnostic tests is an absolute priority. The current prospective study was designed to assess diagnostic performances of an antigen-based rapid detection test (COVID-VIRO) in a real-life setting. Methods Two nasopharyngeal specimens of symptomatic or asymptomatic adult patients hospitalized in the Infectious Diseases Department or voluntarily accessing the COVID-19 Screen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…Furthermore, analytical performances of comparable order as those of our study Ag-RDT were previously reported for some Ag-RDTs in lateral ow immunoassay format [7,9,21,[25][26][27][28][29][30][31][32][33][34][35], while several studies have reported much lower sensitivity levels contrasting with always high speci city [3,[36][37][38][39][40][41]. For example, a comparable Ag-RDT such as the novel COVID-VIRO® from AAZ (Boulogne Billancourt, France) showed a sensitivity of 96.7% and a speci city of 100% in a real-life community setting [31]. In addition, the Ag-RDT RDT BIOSYNEX COVID-19 Ag BSS ful lled also the current recommendations of the French High Authority of Health (Haute Autorité de santé, Saint-Denis, France) for a screening Ag-RTD stating that, at minimum, Ag-RDTs would need to correctly identify signi cant proportions of symptomatic patients (sensitivity ≥ 80%) as well as asymptomatic individuals (sensitivity ≥ 50%) and would have very high speci city (≥ 90%) [42].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Furthermore, analytical performances of comparable order as those of our study Ag-RDT were previously reported for some Ag-RDTs in lateral ow immunoassay format [7,9,21,[25][26][27][28][29][30][31][32][33][34][35], while several studies have reported much lower sensitivity levels contrasting with always high speci city [3,[36][37][38][39][40][41]. For example, a comparable Ag-RDT such as the novel COVID-VIRO® from AAZ (Boulogne Billancourt, France) showed a sensitivity of 96.7% and a speci city of 100% in a real-life community setting [31]. In addition, the Ag-RDT RDT BIOSYNEX COVID-19 Ag BSS ful lled also the current recommendations of the French High Authority of Health (Haute Autorité de santé, Saint-Denis, France) for a screening Ag-RTD stating that, at minimum, Ag-RDTs would need to correctly identify signi cant proportions of symptomatic patients (sensitivity ≥ 80%) as well as asymptomatic individuals (sensitivity ≥ 50%) and would have very high speci city (≥ 90%) [42].…”
Section: Discussionsupporting
confidence: 74%
“…Finally, the Ag-RDT RDT BIOSYNEX COVID-19 Ag BSS ful lled the current WHO's recommendations for a screening Ag-RTD stating that, at minimum, Ag-RDTs would need to correctly identify signi cantly more cases than they would miss (sensitivity ≥ 80%) and would have very high speci city (≥ 97-100%) [20]. Furthermore, analytical performances of comparable order as those of our study Ag-RDT were previously reported for some Ag-RDTs in lateral ow immunoassay format [7,9,21,[25][26][27][28][29][30][31][32][33][34][35], while several studies have reported much lower sensitivity levels contrasting with always high speci city [3,[36][37][38][39][40][41]. For example, a comparable Ag-RDT such as the novel COVID-VIRO® from AAZ (Boulogne Billancourt, France) showed a sensitivity of 96.7% and a speci city of 100% in a real-life community setting [31].…”
Section: Discussionsupporting
confidence: 55%
“…After removing duplicates, 8,921 articles were screened, and 266 papers were considered eligible for full-text review. Of these, 148 were excluded because they did not present primary data [13,19131] or the Ag-RDT was not commercially available [16,132164], leaving 133 studies to be included in the systematic review (Fig 1) [4,165296].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Cerutti et al conducted a trial with 330 patients and only a minority of frozen samples was included (n = 13); this trial was included in our criteria 26 . In the other hand, a prospective study by Courtellemont et al 27 was not included in analysis as known positive patients were pre-selected to enroll; therefore, operators knew the status of the patients beforehand. A similar situation happened in the study conducted by Ghofrani et al 28 , which conducted an comparison with known positive patients and selected eligible samples; the methodology of this study was not clear and the sensitivity, reported as 96.7%, is much higher than usually reported in literature for antigen assays 29 .…”
Section: Methodsmentioning
confidence: 99%